Analisa Pengaruh Professionalism dan Rewards Terhadap Job Satisfaction Serta Implikasinya Pada Organizational Commitment; Telaah Pada Sopir Taksi Konvensional Bandara Soekarno-Hatta - Aldo Winata (Ultima Management : Jurnal Ilmu Manajemen, 2017)
Jakarta is the place where the largest number of land transportation in Indonesia, according to Djarot in Kompas.com article, vehicles every day increased about 1500 units. And according to an article from Liputan 6, revenue from conventional taxi drivers dropped dramatically after the entry of online transport by 40-50% during 2016 due to the entry of online transport. Conventional taxi companies must immediately anticipate this phenomenon so that their human resources can survive in the company. The purpose of this research are first, to know is there a positive effect from professionalism factors to organizational commitment and job satisfaction. Second, to know job satisfaction factors have a positive effect to organizational commitment. And the last is to know is there a positive effect from rewards factors to job satisfaction and organizational commitment’s factors. This research uses descriptive method with non-probability method. Through judgmental sampling technique, primary data collection was obtained from questionnaire distribution to conventional taxi driver of Soekarno-Hatta Airport. The data has been collected and then obtained by using Structural Equation Modeling (SEM). The result of this research indicates that there is positive influence from professionalism to organizational commitment but the data do not support the hypothesis, there is positive influence from professionalism to job satisfaction, but there’s negative effect between job satisfaction and organizational commitment, there is positive relation of rewards to job satisfaction, Finally there is a positive effect of rewards on organizational commitment. Keywords: organizational commitment, professionalism, rewards, job satisfaction, ecommerce, conventional taxi driver.